Industrial Training Report: Perbadanan Perpustakaan Awam Kedah / Nabilah Filzah Abdullah - Abdullah, Nabilah Filzah (Faculty of Information Management, 2018)
After successfully completed my study at campus about 6 semesters, I choose Perbadanan Perpustakaan Awam Kedah (PPAK) to continue my industrial training before graduate. On 1st August 2018, I started to do my practical training and this training duration is about 5 month started from 1 August 2018 until 31 December 2018. I choose this organization because I think I will get a lots of new things and gained a lot of knowledge in every department. Through this practical training, I have learning the real situation to be a librarian. Moreover, I also can gain knowledge from my previous experience while rm study and apply it to settle up my task while in practical training such as cataloging, designing a poster handle library tours and other. Lastly, after facing many challenges, problems and barrier make me take that situation as my experience and learn that all problem have a solution and never give up. I hope with this experiences and knowledge gain through this training. l would be able to manage it easily.